Cesarean section delivery at a tertiary care center - Bhatt, Miti V.; Patel, Arti J.; Solanki, Sonal M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: With the better surgical techniques, better anesthesia and with use of prophylactic antibiotics, cesarean sections are now considered a relatively common and safe operative procedures. Cesarean section is carried out with an incision on anterior abdominal wall and delivery of fetus by laparotomy. There may be an unambiguous association between cesarean delivery and fetomaternal morbidity and mortality. Rising trend in cesarean section deliveries need to be analysed and its effect on fetomaternal outcome at tertiary care centers. Methods: This retrospective study was carried out with the aim to study the trends in cesarean section deliveries over the period extending from March 2022 to March 2024 has included all cesarean section delivery cases fulfilling the inclusion and exclusion criteria. The data were collected from the medical record department (MRD) and was kept confidential, and privacy of the patients were maintained, and data was analysed as per predefined proforma. Results: The cesarean section rate was 49.11% out of 2596 deliveries, out of which most common indication being previous CS (37.89%) followed by fetal distress (18.24%). Majority of cases belonged to Robson group 5 followed by group 2. Emergency CS 61.72%, some neonatal complications were seen in which major cause was respiratory distress (9.88%). No fetomaternal mortality occurred during the study period. Conclusions: Although with advent technology and medical advancement cesarean section is being a much safer and better operative procedure but its impact on future pregnancies and morbidity related to it should be kept in mind. The audit regarding the rate, indications and complications related to cesareans section should be analysed in all health care facilities.